Lightning electromagnetic transient characteristics of the space launch site. (December 2020) - Zhu, Degui; Xiang, Nianwen; Li, Wei; Dong, Bingbing; Yang, Jin; Wan, Yihu
Abstract: The direct lightning protection system of the space launch site can achieve effective protection against direct lightning. However, the lightning electromagnetic pulse cannot be ignored while the rocket waiting on the platform. The three-dimensional lightning transient electromagnetic model is established by method of moments, when the launch site is struck by direct lightning. In order to quantitatively evaluate lightning environment of the launch site, electromagnetic fields of launch area are calculated in this paper with a size of 40 × 40 m 2 on the ground and at 40 m above ground. When the lightning current is 200 kA in the case of severe lightning, the simulation results of basic parameters show that magnetic field on the ground is much larger than 40 m above ground, and the maximum and minimum values of magnetic field on the ground are respectively 608 A/m (7.6Gs) and 95 A/m (1.2Gs). The electric field at 40 m above ground is much larger than the ground, and the maximum and minimum values of electric field at 40 m above ground are respectively 111 kV/m and 26 kV/m. Under six different factors, the three factors of number of shielded wires, distance between lightning towers and lightning current wave-front parameters have obvious effects on the electromagnetic field in the launch area. The highest and lowest reduction rates of electromagnetic fields are about 88% and 33% respectively. However, other factors reduce electromagnetic fields by no more than 13%. The critical magnetic field for permanent damage of electronic equipment is 2.4Gs, which is between the minimum and maximum magnetic fields of the launch area. It is recommended that electronic equipment is placed in area with smaller magnetic field, which is close to the center of the launch area. This paper provides a reference for the lightning protection indicators and suggestions for the space launch site.